the Contribution of Internet Use and Achievement Motivation toward Student Study Skill - Walidaini, Birrul; Miko, Nopri Abadi; Delano, Vasco (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2025)
Study skills refer to cognitive, behavioral, and self-regulatory abilities that support effective learning. Many students still show poor study skills, and factors such as internet use and achievement motivation may influence them, as online information access and a strong drive to achieve can shape learning strategies. This research aims to examine the contribution of internet use and achievement motivation toward students’ study skills. The study used a quantitative approach with a descriptive correlational method. The population consisted of 625 students, and 244 Guidance and Counseling majors at Universitas Negeri Padang were selected as samples. Instruments were based on a Likert scale with reliability values of 0.841, 0.841, and 0.842. Data were analyzed using multiple regression, although the manuscript does not clearly explain the research design or descriptive statistical procedures. The findings show that both variables contribute 31.3% to study skills, with a significant positive relationship.